Halo concentrations and weak-lensing number counts in dark energy cosmologies - Bartelmann, Matthias; Perrotta, Francesca; Baccigalupi, Carlo (Arxiv, 2002)
We study the effects of a dark energy component with equation of state p=w rho with constant w >= -1 on the formation of Cold Dark Matter (CDM) haloes. We find two main effects: first, haloes form earlier as w increases, and second, the amplitude of the dark-matter power spectrum gets reduced in order to remain compatible with the large scale Cosmic Microwave Background (CMB) anisotropies. These effects counteract. Using recipes derived from numerical simulations, we show that haloes are expected to be up to ~ 50% more concentrated in CDM models with quintessence compared to Lambda-CDM models, the maximum increase being reached for w ~ -0.6. For larger w, the amplitude of the power spectrum decreases rapidly and makes expected halo concentrations drop. Halo detections through weak gravitational lensing are highly sensitive to halo concentrations. We show that weak-lensing halo counts with the aperture-mass technique can increase by a factor of ~ 2 as w is increased from -1 to -0.6, offering a new method for constraining the nature of dark energy.
Gesehen am 26.09.2017